Conocimiento actual de los Trogidae de Chile (Coleoptera: Scarabaeoidea) - Dieguez, V.M.
(Es, En)
Ilus., 8 ref.
Keywords: COLEOPTERA; SCARABAEOIDEA; TAXONOMIA; CHILE; POLYNONCUS; REVISTA CHILENA DE ENTOMOLOGIA